Study of Absolute Neutrophil Absolute Lymphocyte count ratio in Community Acquired Pneumonia patients as a prognostic indicator at a tertiary care centre - Nirgude, Dyaneshwar; Malge, Mahadev Hanmantappa; Rajoli, Swetha; Rajanna, Avinash Hanbe (Asian Journal of Medical Sciences, 2021)
Background: Community acquired pneumonia refers to pneumonia contracted by a person with little or no contact with health care system. Following endotoxemia the number of circulating neutrophils increases while lymphocyte counts decrease. Combining both parameters seems a logical step and the ratio of neutrophil and lymphocyte counts is increasingly used in several clinical circumstances. Initially, this so-called neutrophil-lymphocyte count ratio (NLCR) was studied as an infection marker in ICU patients and found to correlate well with disease severity and outcome, according to APACHE-II and SOFA scores. In the current study, we explored the value of the NLCR in patients admitted with Community acquired pneumonia. Aims and Objectives: 1) To find out the value of Neutrophil-Lymphocyte Count Ratio (NLCR)in Community Acquired Pneumonia (CAP). 2) To study Neutrophil-Lymphocyte Count Ratio (NLCR) as prognostic indicator in Community Acquired Pneumonia (CAP). Materials and Methods: This prospective study was conducted on minimum of 100 patients admitted to hospitals from November 2015 to September 2017 from Bangalore. After admission of cases based on CURB-65 scores, a detailed history and clinical examination was done along with chest x-ray to establish the diagnosis. Before taking into the study all patients had signed the informed consent. Routine haematological investigations done on day 1,3 & 7 were carried out. Serum c-reactive protein levels, Urea nitrogen levels, Sputum for culture and sensitivity and Acid-fast bacilli (AFB) was done on the same day of admission. ANC (Absolute neutrophil count), ALC (Absolute lymphocyte count) and NLCR were calculated. Results: Our study included age groups above 18yrs. Majority of the patients in the study were between 58-67 years (30%) followed by 48-57 years (27%). As the CURB-65 score increased from score 0 to score 4–5, the NLCR consistently increased, while the lymphocyte counts consistently decreased. In patients who died there was a significantly higher NLCR at presentation compared to patients that survived (15.18±3.55 versus 11.73±3.01, p-value,0.003). Conclusion: In our study increased NLCR carried poor prognosis which correlated with high CURB65 score and ICU admission. In patients who died there was a significantly higher NLCR at presentation compared to patients those survived.